Effects of Anosognosia on Static and Dynamic Amplitudes of Low-Frequency Fluctuation in Mild Cognitive Impairment - Fu, Yanv; Luo, Xiao; Zeng, Qingze; Li, Kaicheng; Zhang, Tianyi; Li, Zheyu; Xu, Xiaopei; Hong, Luwei; Chen, Yanxing; Zhang, Minming; Liu, Zhirong (Frontiers in Aging Neuroscience, 2021)
Background: Anosognosia is a significant symptom in patients with mild cognitive impairment (MCI) while the underlying neurological mechanism behind which is still unclear. Methods: A total of 121 subjects were included and classified into three groups, including 39 normal controls (NC), 42 MCI without anosognosia (MCI-NA), and 40 MCI with anosognosia (MCI-A), based on their Everyday Cognition (ECog) questionnaire (discrepancy score). Resting-state functional MRI were acquired from all subjects, and the static amplitudes of low-frequency fluctuation (sALFF) and dynamic ALFF (dALFF) variance were investigated to evaluate the intrinsic functional network strength and stability, respectively. Eventually, correlation analyses were conducted to explore the relationship between brain activity changes and cognitive status in all subjects. All analyses were corrected by grey matter volume and age. Results: No significant difference was found between MCI-A and MCI-NA (P >0.05) in cognitive ability. Regarding intrinsic brain activity, MCI-A had increased sALFF and dALFF variance in the anterior cingulate cortex (ACC) relative to MCI-NA, as well as decreased sALFF and dALFF variance in the precuneus relative to MCI-NA and controls. Moreover, MCI-A had decreased sALFF in the inferior temporal gyrus (ITG) and paracentral lobule (PCL) compared to MCI-NA. Among all subjects, correlation analyses showed that the sALFF and dALFF variance in precuneus was related to the Ecog discrepancy score (r=0.215 and 0.223, respectively) and delayed story recall (r=0.225 and 0.267, respectively). Conclusion: Alterations of intrinsic brain activation in ACC and precuneus may account for the anosognosia symptom in MCI patients.